“The disgust of the community against hanging”: The Execution of Bennie Swim and the Debate over Capital Punishment in New Brunswick - Boudreau, Michael (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2022)
This article examines the bungled execution of Bennie Swim in Woodstock, New Brunswick, in 1922 following his trial and conviction for the murder of Olive Swim Trenholm. It explores the criticism over Swim’s execution and the subsequent debate about capital punishment, including whether hanging was a humane method of executing a condemned prisoner. It also assesses the social construction of the rural New Brunswicker as a “beast of the field” and rural New Brunswick as the “bad lands,” and how these images informed some observers’ views of Olive Swim Trenholm and Bennie Swim, including his actions and his execution.